Difference in Therapeutic Response Between Basal and Nonbasal Triple‐Negative Breast Cancers. (19th August 2013) - Bertucci, François; Finetti, Pascal; Viens, Patrice; Birnbaum, Daniel
Abstract : This study, which nicely complements a study recently published in The Oncologist, shows for the first time that triple‐negative breast cancers are much more heterogeneous than basal breast cancers regarding the response to chemotherapy and the probability of response to molecularly targeted therapies.